2013
DOI: 10.1088/1674-1056/22/12/120402
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency gravitational waves having large spectral densities and their electromagnetic response

Abstract: Various cosmology models, brane oscillation scenarios, interaction of interstellar plasma with intense electromagnetic radiation, and even high-energy physics experiments (e.g., Large Hadron Collider (LHC)) all predict high frequency gravitational waves (HFGWs, i.e., high-energy gravitons) in the microwave band and higher frequency region, and some of them have large energy densities. Electromagnetic (EM) detection to such HFGWs would be suitable due to very high frequencies and large energy densities of the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…We notice that, as typical for HFGW detection, higher frequencies can compensate for low strains [44]. The time-averaged flux (36) is at the O(h 2 ) order, thus comparable to the vacuum inverse-Gertsenshtein effect [21].…”
Section: The High Frequency Gravitational Wave Detectormentioning
confidence: 87%
“…We notice that, as typical for HFGW detection, higher frequencies can compensate for low strains [44]. The time-averaged flux (36) is at the O(h 2 ) order, thus comparable to the vacuum inverse-Gertsenshtein effect [21].…”
Section: The High Frequency Gravitational Wave Detectormentioning
confidence: 87%
“…We can find that, Ω gw in cells with larger distance than these shaded cells, will have too low energy density for potential detection (e.g. in proposed HFGW detectors [16][17][18][19][20]), and cells with shorter distance than these shaded cells can have higher Ω gw but will lead to stronger GRB power which would be dangerous to life and existing ecological systems on Earth. Therefore, the shaded cells in Table I present optimal range of Gamma-HFGW sources with proper distance and suitable power (in safe level near globe) to be potentially observational targets of HFGWs from the Earth.…”
Section: Gamma-hfgws From Magnetars and Grbsmentioning
confidence: 99%
“…Nevertheless, for other cases which cannot provide sizable far field effect on the Earth, such as more faraway GRBs, the possibility still would not be excluded that in the future some spacecraft-based HFGW detector approaching closer area to such sources or some Earth-based detector with greatly enhanced sensitivity would also might be able to capture these Gamma-HFGWs. Some proposed HFGW detection system [16][17][18][19][20] is especially sensitive to GWs in very high-frequency bands. E.g., the Gamma-HFGWs (Ω gw ∼ 10 −6 ) would generate the firstorder perturbed signal EM waves having power of ∼ 10 −20 W att per m 2 in such planned detection system.…”
Section: Gamma-hfgws From Magnetars and Grbsmentioning
confidence: 99%
“…On the other hand, according to contemporary observations, there are very widespread background galactic magnetic fields (GMFs, strength around ∼ 10 −10 to 10 −9 Tesla) [28] within the Milky way. Therefore, according to the electrodynamics in curved spacetime, in the frame of EM response to GWs, we propose that such high-frequency GWs of sub-solar mass PBH binary mergers will interact with the GMFs in the Milky The effect of EM response to GWs had been long studied [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], and previous works [30,[35][36][37]45] indicated that the strengths of perturbed EMWs depends on both strengths and spatial scales (accumulation distance) of the background magnetic fields. Thus, the GMFs will provide a huge accumulation distance to compensate the weakness of their very low strengths, and then would lead to considerable EM signals.…”
Section: Introductionmentioning
confidence: 99%